The Chief Officer of Corporate Social Responsibility: A Study of Its Presence in Top Management Teams - Strand, Robert (2013)
I present a review of the top management teams (TMTs) of the largest public corporations in the U.S. and Scandinavia (one thousand in total) to identify corporations that have a TMT position with “corporate social responsibility” (CSR) or a “CSR synonym” like sustainability or citizenship explicitly included in the position title. Through this I present three key findings. First, I establish that a number of CSR TMT positions exist and I list all identified corporations and associated position titles. Second, I show that Scandinavian corporations are significantly more likely than U.S. corporations to have such CSR TMT positions. This finding serves as evidence that the U.S. may have been surpassed by a subset of Europe, i.e., Scandinavia, in at least one relevant measure of explicit CSR, whereby this study may serve witness to a noteworthy juncture post Matten and Moon’s (Academy of Management Review, 33(2):404–424, 2008) “Implicit & Explicit CSR” article. And third, I show that corporations with a CSR TMT position are three times more likely to be included in the Dow Jones Sustainability Index (DJSI) than corporations with none. A range of further research opportunities stemming from these findings include exploring whether explicit attention to CSR by the corporation is indicative of a longer term trend that has to do with attention to responsible business and whether a move away from the expression ‘CSR’ toward the expression ‘sustainability’ is underway and what this may entail.
Keywords: Explicit CSR; U.S; Scandinavia; Top management team; C-Suite; Chief Sustainability Officer; Chief Officer of CSR